Case study of the design and execution of the drainage system for the soccer pitch at Bezerrão Stadium (International Seven Journal of Multidisciplinary, 2024)
In soccer stadiums, every aspect is important. Infrastructure, stands, changing rooms, artificial lighting and, without a doubt, the pitch, which is vital if matches are to run smoothly and without risk. One of the problems that reduces playability is water puddles, i.e. the waterlogging of the pitch caused by rainwater. This problem is common in Brazil due to the equatorial tropical climate, which is characterized by high temperatures and intense rainfall, the latter causing, in some situations, cancellations of matches with inconvenience to fans and spectators and even delays in championships. Another problem caused by excessive accumulated water is damage to the health of the grass, as poor drainage prevents the correct development of the root system due to the lack of oxygen in the soil, limiting the absorption of nutrients, which are important for the development of the grass, and making the grass maintenance and mowing process more difficult. Within this context, the drainage system on a soccer pitch is essential. This system is divided into surface and subsurface. Therefore, this paper presents and discusses the drainage system of the Bezerrão Stadium soccer field, located in the Administrative Region of Gama, Federal District.